Psychometric properties of comprehensive cognitive, affective, and psychomotor competency assessment scales in psychodynamic psychotherapy for borderline personality disorder - Lukman, Petrin Redayani; Wiguna, Tjhin; Soemantri, Diantha; Menaldi, Sri Linuwih; Elvira, Sylvia Detri; Sutanto, Limas; Sapiie, Tuti Wahmurti A.; Kekalih, Aria; Noviasari, Reina Rahma; Rizki, Hukma Shabiyya; Giyani, Kharisma Zatalini (Frontiers in Psychiatry, 2024)
BackgroundPsychodynamic psychotherapy is a type of psychotherapy for individuals with borderline personality disorder (BPD). However, competency in conducting effective psychodynamic psychotherapy for BPD is difficult to evaluate. Therefore, this study aimed to identify the psychometric properties of a comprehensive scale to assess cognitive, affective, and psychomotor competencies (CS-CAPC) in psychodynamic psychotherapy for BPD.MethodsThis is a qualitative study. The first step used the Delphi technique to gather experts’ opinions on the cognitive, affective, and psychomotor competencies necessary to conduct psychodynamic psychotherapy for BPD. The experts comprised three psychotherapists, seven psychiatrists with experience in psychotherapy, and nine teaching staff. A panel discussion was conducted to obtain qualitative data. Thematic data analysis was adopted, and content validity testing was used to analyze the content validity of the CS-CAPC in psychodynamic psychotherapy for BPD.ResultsThe CS-CAPC comprised two scales assessing two specific competencies in psychodynamic psychotherapy for BPD: The first scale, the psychodynamic formulation competency assessment scale (PF-CAS), comprised six items, including the case description, etiology, and potential course of therapy. The second scale, the practical-competency assessment scale (PC-CAS) for psychodynamic psychotherapy for BPD, comprised 12 items, including building a therapeutic alliance, performing psychodynamic interventions while working through the therapeutic process, and closing the session. The scale-level content validity index (S-CVI) for the PF-CAS was 0.981, and that for the PC-CAS in psychodynamic psychotherapy for BPD was 1.00.ConclusionThe CS-CAPC in psychodynamic psychotherapy for BPD had good validity in assessing individual competency in the cognitive, affective, and psychomotor domains.